PELATIHAN PENANGANAN DAN PENCEGAHAN PERUNDUNGAN BAGI GURU-GURU DI SD NEGERI NOMOR 25 KOTA SELATAN GORONTALO - Haris Munandar; Erga Kurniawati; Thayban Thayban; Ryan Humardani Syam Pratomo (Universitas Katolik Widya Karya Malang, 2023)
Community service activities on bullying prevention and handling aim to increase awareness, understanding, and countermeasures against bullying in schools. Service activities are carried out through identification of needs, material development, implementation of counseling, and evaluation. Teachers are given training on bullying handling, effective communication strategies, conflict management, social skills development, and mental strengthening. They are also given an understanding of human rights, tolerance, empathy, and the importance of building healthy relationships in schools. The results of the service activities show an increase in teachers' awareness and understanding of bullying and the development of a safe and inclusive school environment. The collaboration of all relevant parties in dealing with bullying can create positive change, reduce bullying rates, and create a better environment for students in their learning and development process.